Fundamental of Entrpreneurship ENT300 : Fabric Printing Enterprise/ Rick Tj Sikat@Modiley... [et al.] - Sikat@Modiley, Rick Tj; Abdul Rashid, Abdul Hafiz; Makil, Muhammad Nazri; Balan, Dominic (2012)
This business is based on partnership which consists of four members. This business has general and administration manager which hold by one person in one time. marketing manager, operation manager and financial manager. The main activity of our business is printing and embroidery service. Our main target customers are students. This is because of our premise is nearest to University such as Uitm, Unimas and IPEG. Our premise is located at the Desa Ilmu, Kota Samarahan Sarawak. Our business will operate form 8.00am until 5.00pm (Monday-Thursday) and close on Sunday and public holiday. Inorder to produce good quality of services, there are some criteria that have to fulfil, for instance continuously giving effort. This is also to make the business position in the first place position. Every partners are compulsory involve in the business management. We have agreed that Rick t.j bin Sikat as the general and administration manager, Abdul Hafiz b Abdul Rashid as the marketing manager, Muhd Nazri Makil as the operation manager and the last one. Dominic Ak Balan as the financial manager. The selection of that status is based on the experience, skills and ability.